KERJAYA GRADUAN SARJANA MUDA SYARIAH, AKADEMI PENGAJIAN ISLAM, UNIVERSITI MALAYA (1996 - 2002) - Ali, Nor Aini (Jurnal Syariah, 2019)
This study examines career of the graduates of bachelor of Shariah, Academy of Islamic Studies, University of Malayafrom 1996 - 2002 by using a questionnaire to collect the data. A total of 190 respondent who are served by a questionnaire are analysed by using parametric test and non parametric test. The finding shows that majority graduates (89%) are working, whereby 7.9% of the graduates opting tofurther their studies and the rest of the respondent (3.2%) remain unemployed during one year after graduation. From the total of working graduates, it is analysed that 54.4% involve in education field. This study also shows that at current, majority of the respondent (85.8%) are employed in various of sector andfield.